Coping strategies in livestock-dependent households in East and southern Africa: a synthesis of four case studies - Thornton, Philip K.; Boone, Randall B.; Galvin, K.A.; BurnSilver, S.B.; Waithaka, M.M.; Kuyiah, J.; Karanja, S.; González Estrada, E.; Herrero, Mario (Springer, 2007)
Integrated assessment seeks to combine models of the ecological as well as the social system to allow different scenarios to be tested in terms of their likely impacts on ecological functioning and household well-being. We outline such work undertaken in four case studies in East and southern Africa: pastoralist communities in northern Tanzania, agro-pastoralists in southern Kenya, communal and commercial ranchers in South Africa, and mixed crop-livestock farmers in western Kenya. Results from these case studies are synthesised to test the hypothesis that households’ capacity to adapt in the face of increasing external stresses is governed by flexibility in livelihood options. The results support this hypothesis. There is considerable variation in how households in these places cope with external stresses. Options include intensification, diversification, and increasing off-farm economic activities, and these depend on household objectives and attitudes as well as on access to natural resources, inputs and output markets. The results also indicate that generally it is the poorer households that can gain the most from implementing such options for coping and managing risk. Quantifying likely household and ecosystem impacts of different options is a crucial step in targeting appropriate technology, policy and adaptation interventions in the face of considerable system changes. We conclude with some research needs to improve integrated assessment tools that may allow us to represent more realistically the highly complex decision-making milieu of householders in sub-Saharan Africa who are dependent on ecosystem goods and services for a large part of their livelihoods.